Crystal Structures and Phase Sequences of Metallocenium Salts with Fluorinated Anions: Effects of Molecular Size and Symmetry on Phase Transitions to Ionic Plastic Crystals. Issue 44 (21st September 2016) - Mochida, Tomoyuki; Funasako, Yusuke; Ishida, Mai; Saruta, Shingo; Kosone, Takashi; Kitazawa, Takafumi
Abstract: Sandwich compounds often exhibit various phase transitions, including those to plastic phases. To elucidate the general features of the phase transitions in metallocenium salts, the thermal properties and crystal structures of [Fe(C5 Me5 )2 ]X ([1 ]X), [Co(C5 Me5 )2 ]X ([2 ]X), and [Fe(C5 Me4 H)2 ]X ([3 ]X) have been investigated, where the counter anions (X) are Tf2 N (=(CF3 SO2 )2 N − ), OTf (=CF3 SO3 − ), PF6, and BF4 . The Tf2 N salts commonly undergo phase transitions from an ordered phase at low temperatures to an anion‐disordered phase, followed by a plastic phase and finally melt at high temperatures. All these salts exhibit a phase transition to a plastic phase, and the transition temperature generally decreases with decreasing cation size and increasing anion size. The crystal structures of these salts comprise an alternating arrangement of cations and anions. About half of these salts exhibit phase transitions at low temperatures, which are mostly correlated with the order–disorder of the anion. Abstract : Organometallic ionic plastic crystals : Metallocenium salts [M(C5 Me5 )2 ]X (M=Fe, Co) and [Fe(C5 Me4 H)2 ]X with fluorinated anions commonly exhibit ionic plastic phases. With increasing temperature, these salts mostly undergo phase transitions from an ordered phase to an anion‐disordered phase and then to a plastic phase. The crystal structures and transition temperatures are correlated with the cation/anion radius ratio.